Resistance of Shia Minority Students in Educational Institutions in Jember, East Java, Indonesia - Mochammad Zaka Ardiansyah; Akrimi Matswah (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
Discrimination against religious minorities in educational institutions is a global issue that undermines the principles of a love-based curriculum and ecotheology promoted by the Ministry of Religious Affairs of the Republic of Indonesia. This article investigates the typology of resistance enacted by Shia minority students within Islamic Religious Education classes and youth organizations. Employing a retrospective narrative inquiry, the study explores the past experiences of five Shia minority students regarding their resistance in these educational settings at both school and university levels. To ensure research ethics and protect the confidentiality of individuals from marginalized minority groups, all participant identities and educational institution names are presented using pseudonyms. Participants were recruited through snowball sampling and interviewed using the life story interview method. Field data were analyzed using the resistance theories of Solorzano & Villalpando, Solorzano & Bernal, and McFarland, as well as thematic analysis techniques from Braun and Clarke. The findings indicate that Shia minority students engaged in three forms of resistance: covert, passive, and conformist. This article contributes new insights to the scholarship on Islamic Religious Education and expands understanding of Muslim minority students' resistance, including resistance within educational institutions.